2020
DOI: 10.1021/acs.orglett.0c00554
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Cross-Coupling of Alkyl Carboxylic Acid Derivatives with Pyridinium Salts via C–N Bond Cleavage

Abstract: The electrophile−electrophile cross-coupling of carboxylic acid derivatives and alkylpyridinium salts via C−N bond cleavage is developed. The method is distinguished by its simplicity and steers us through a variety of functionalized ketones in good to excellent yields. Besides acid chlorides, carboxylic acids were also employed as acylating agents, which enabled us to incorporate acid-sensitive functional groups such as MOM, BOC, and acetal. Control experiments with TEMPO revealed a radical pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 91 publications
1
21
0
1
Order By: Relevance
“…The developed protocol can be used in step-economical syntheses of natural products based on cyclopropanol-ring cleavage strategies, along with generation of molecular libraries from the single cyclopropanol precursor in the framework of diversity-oriented synthesis paradigm. Furthermore, in view of general importance of acyl-transfer reactions from mixed anhydrides [49,87,88], the new method of their generation could serve as a beneficial supplement to the existing approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The developed protocol can be used in step-economical syntheses of natural products based on cyclopropanol-ring cleavage strategies, along with generation of molecular libraries from the single cyclopropanol precursor in the framework of diversity-oriented synthesis paradigm. Furthermore, in view of general importance of acyl-transfer reactions from mixed anhydrides [49,87,88], the new method of their generation could serve as a beneficial supplement to the existing approaches.…”
Section: Discussionmentioning
confidence: 99%
“…3 Rasappan and co-workers contributed to the growing list of reactions by coupling acyl chlorides with Katritzky salts to form ketones in the presence of NiBr 2 •bpy (5−10 mol %) and Mn (1.8 equiv) as the reductant in a acetonitrile/N,Ndimethylacetamide (DMA) mixture (95:5) at room temperature. 48 A broad substrate scope was observed, and the products were isolated in good yields. However, the need to use 2 equiv of distilled acyl chloride is a limitation of this method.…”
Section: ■ Recent Reports On Ni-catalyzed Reactionsmentioning
confidence: 95%
“…Several recent advances utilizing Katritzky salts as coupling partners were highlighted in the first installment of this review series . Rasappan and co-workers contributed to the growing list of reactions by coupling acyl chlorides with Katritzky salts to form ketones in the presence of NiBr 2 ·bpy (5–10 mol %) and Mn (1.8 equiv) as the reductant in a acetonitrile/ N , N -dimethylacetamide (DMA) mixture (95:5) at room temperature . A broad substrate scope was observed, and the products were isolated in good yields.…”
Section: Recent Reports On Ni-catalyzed Reactionsmentioning
confidence: 99%
“…Other electrophiles have also been engaged in this Ni- catalyzed cross-coupling reactions with Katritzky salts. For example, Matsuo, 137 Rasappan 138 and Watson and Weix 139 have independently reported the syntheses of ketones from pyridinium salts 175 or 200 (Scheme 78). Matsuo demonstrated that N -acylsuccinimides 201 react in the presence of NiBr 2 and 1,10-phenanthroline (1,10-phen) with the assistance of one equivalent of MgCl 2 as Lewis acid and Mn as reducing agent to afford ketones 202 .…”
Section: Pyridine Derivativesmentioning
confidence: 99%